"Ethics surrounding the provision of abortion care". (August 2017) - Faúndes, Anibal; Miranda, Laura
Abstract : The provision of abortion care represents a great ethical challenge to physicians, particularly in countries where the law states that abortion is a crime. The concept that it is a crime carries a stigma that is worse than that associated with other acts qualified by law as crimes. This stigma leads to at least two different kinds of unethical behavior. One is the refusal to provide safe abortion services to women who comply with the legal requirements, alleging conscientious objection, and the other is to discriminate against women with complications of induced abortion. Both unethical behaviors may be associated with severe consequences for the health of women whose care was refused or delayed. Less attention is given to the ethical obligation to prevent induced abortion from recurring by offering postabortion contraception to comply with the ethical obligation of preventing harm to the patients for whose care they are responsible.